HEALTH PROTOCOL EDUCATION BY DISTRIBUTING LEAFLETS AND IMMUNE BOOST HERBAL AT KIO SPORT - ahmad riadi (Poltekkes Kemenkes Semarang, 2024)
Background: Education on Health Protocols by distributing leaflets and immune-boosting herbs at Kio Sport and Purwomukti Sport. The target group for this community service is members of the Taruna badminton club and the Bintang club, totaling 50 people, consisting of 25 Â Bintang Badminton Â club members and 25 .Optimization of these two groups is expected to have a significant impact in improving skills and insight in implementing health protocols and knowing herbal ingredients to increase the body's immune system.This method of implementing community service takes place at Kio Sport on Tuesday and Thursday nights, while at Purwomukti Sport on Tuesday and Sunday nights, education is carried out by distributing leaflets and discussion interviews in the form of FGDs preceded by a pre-test and post-test via Google Form. do this by minimizing physical contact or by considering health protocols. It is hoped that the output of this community service after completion will produce scientific articles and ongoing collaboration with PB Bintang and PB Taruna.Â